2023
DOI: 10.3847/2041-8213/ace18b
|View full text |Cite
|
Sign up to set email alerts
|

The NANOGrav 15 yr Data Set: Constraints on Supermassive Black Hole Binaries from the Gravitational-wave Background

Abstract: The NANOGrav 15 yr data set shows evidence for the presence of a low-frequency gravitational-wave background (GWB). While many physical processes can source such low-frequency gravitational waves, here we analyze the signal as coming from a population of supermassive black hole (SMBH) binaries distributed throughout the Universe. We show that astrophysically motivated models of SMBH binary populations are able to reproduce both the amplitude and shape of the observed low-frequency gravitational-wave spectrum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(74 citation statements)
references
References 195 publications
3
70
0
1
Order By: Relevance
“…To calculate the estimates conditioned on the GWB parameters in NG15gwb, we use SMBHB populations generated with holodeck (Agazie et al 2023d), following semianalytic prescriptions for galaxy stellar mass function (GSMF), galaxy pair fraction, galaxy merger time, and black hole-bulge mass relations. These populations are then evolved in time using a self-consistent binary evolution model to produce an expectation value for the number of binaries of each SMBHB parameter (seeAgazie et al 2023d for details).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the estimates conditioned on the GWB parameters in NG15gwb, we use SMBHB populations generated with holodeck (Agazie et al 2023d), following semianalytic prescriptions for galaxy stellar mass function (GSMF), galaxy pair fraction, galaxy merger time, and black hole-bulge mass relations. These populations are then evolved in time using a self-consistent binary evolution model to produce an expectation value for the number of binaries of each SMBHB parameter (seeAgazie et al 2023d for details).…”
Section: Discussionmentioning
confidence: 99%
“…While the source of the GWB is not known for certain, one potential source is a population of inspiraling supermassive black hole binaries (SMBHBs) with masses 10 8 -10 10 M e , whose superposition of quasi-monochromatic GW signals manifests as a stochastic background in our PTA. The inferred demographics and dynamics of such SMBHBs are studied in Agazie et al (2023d). Other processes from the early Universe may contribute to the GWB (see, e.g., Afzal et al 2023 and references therein); however, an expected outcome of an SMBHB-dominated GWB is the presence of signal anisotropy, either through the clustering of host galaxies or Poisson fluctuations in GW source properties (Mingarelli et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the orbital evolution via the three-body interaction between the SMBH binary and stars in the system affects the spectrum in the low-frequency (Sesana et al 2004). Recent PTA observations such as NANOGrav (see, e.g., Agazie et al 2023a andAgazie et al 2023b) imply the importance of the effect of eccentricity and the orbital evolution via environmental interaction from the view of the spectrum of observed GWB. Furthermore, if triple BH interaction occurs in a system, one of three BHs will be ejected, and then the radius of the other two BHs will shrink and lead to their coalescence (Volonteri et al 2003;Bonetti et al 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Kelley et al 2023, in preparation), based on the Illustris cosmological hydrodynamical simulation (Vogelsberger et al 2014). This model applies a postprocessing step to account for small-scale physics not captured by Illustris, uses a phenomenological model to describe binary evolution (for details, see Agazie et al 2023b), and produces a simulated list of binaries in the universe (Kelley et al 2017a(Kelley et al , 2017b(Kelley et al , 2018. To add the contribution of these binaries, we model the brightest 1000 binaries in each frequency bin individually and add the rest as a stochastic background.…”
Section: Realistic Simulated Data Setsmentioning
confidence: 99%
“…PTAs recently reported evidence for a nanohertz stochastic GW background (GWB) in their most recent data sets (Agazie et al 2023a;Antoniadis et al 2023a;Reardon et al 2023;Xu et al 2023), and their results were shown to be consistent with each other (The International Pulsar Timing Array Collaboration et al 2023). The most plausible source of this background is a large collection of supermassive black hole binaries (SMBHBs; Agazie et al 2023b), but other more exotic phenomena can also explain the signal (Afzal et al 2023).…”
Section: Introductionmentioning
confidence: 99%